글루포시네이트 암모늄 제초제 중독환자에서 혈중 암모니아 농도와 사망률과의 연관성에 대한 연구 - 고은나래; Eun Na Lae Ko; 김동훈; Dong Hoon Kim; 이수훈; Soo Hoon Lee; 정진희; Jin Hee Jeong; 이상봉; Sang Bong Lee; 성애진; Aejin Sung; et al. (대한임상독성학회지, 2020)
Purpose: The association of the initial serum ammonia level with in-hospital mortality in patients with acute glufosinate-ammonium herbicide poisoning was studied. Methods: This retrospective cohort study was conducted between March 2012 and August 2019 in the emergency department after glufosinate-ammonium herbicide poisoning. Survivors and non-survivors were analyzed using a Mann-Whitney U test and Fisher’s exact test. Multivariate logistic regression analysis was performed to determine the independent risk factors for mortality. Results: One hundred and six patients were enrolled; 11 died, yielding a mortality of 10.4%. The serum bicarbonate level was significantly lower in the non-survival group than the survival group. Age, serum ammonia, blood urea nitrogen, creatinine levels, SOFA score, and APACHE II score were significantly higher in the non-survival group than the survival group. Age, serum ammonia, and creatinine level were independent risk factors for mortality in multivariate logistic regression analysis. Conclusion: The initial serum ammonia level is associated with mortality in patients with acute glufosinate herbicide poisoning.